Charles A Beard - Alanzy Alanzy, Sarah (My University, 2019)
In my research paper I want to talk about Charles A. Beard's arguments, theories, and ideas reflection on American citizen, which is represented by studying his books and articles. Beard is an American historian who iconoclastic studies of the development of U.S. political institutions. Beard thereafter became one of the intellectual leaders of the Progressive movement and of American liberalism. he has many iconoclastic masterwork sparked a deep historical debate that has not abated. Scrutinizing the Constitution in light of economic forces, covers the nation's history from colonial times to World War I, he was criticizing as a perfect example of an introductory history to the United States of America. Moreover, if you take a look at his book you will get that his books has been selected by scholars as being culturally necessary and the important part of the knowledge base of American civilization and democracy. Also he wrote about the Theory of political economy to explain the conception of the US constitution and the consequential balancing of powers.